GE11-antigen-loaded hepatitis B virus core antigen virus-like particles efficiently bind to TNBC tumor - Zhang, Long; Tang, Lin; Jiang, Yongsheng; Wang, Chenou; Huang, Lijiang; Ding, Ting; Zhang, Tinghong; Li, Huaqiong; Xie, Longteng (Frontiers in Oncology, 2023)
Among all the breast cancer, Triple-negative breast cancer (TNBC), characterized by the lack of expression of estrogen receptor, progesterone receptor, and HER2, is the most metastatic and recurrent subtype. Owning TNBC lacks major effective target molecules, chemotherapy, and surgical intervention remain the main treatment option. Doxorubicin (DOX) is frequently used as part of the adjuvant chemotherapy drug for TNBC chemotherapy, but its adverse effect, mainly caused by its off-target and toxic side effect, has severely limited its clinical application. To address this issue, DOX was encapsulated into different delivery systems, such as nanoparticles (NPs), with an epidermal growth factor receptor (EGFR) target factor. With the advantage of biocompatibility, structural stability, and easy cell endocytosis, virus-like particles (VLPs) are proposed as an effective delivery system. Recently, hepatitis B core protein (HBc) VLPs have been used to develop vaccines. However, utilizing HBc VLPs in the tumor field is rarely attempted. Here, a TNBC tumor-targeting GE11-HBc VLPs is constructed through genetic engineering. The GE11 peptide, a 12 amino acid peptide targeting EGFR, was inserted into the surface protein loops of VLPs. These VLPs possessed excellent stability, DOX loading efficiency, and preferentially released drug payload at high GSH levels. The insertion of GE11 targeting peptide caused improved cellular uptake and enhanced cell viability inhibitory in EGFR high-expressed TNBC cells. Together, these results highlight DOX-loaded, EGFR-targeted VLPs as a potentially useful therapeutic choice for EGFR-overexpressing TNBC.